Code-Switching and Social Media in Bangladesh: Emergence of a New English - Kaniz Anjum Aorny; Md. Nazmul Haque; Md. Mozaffor Hossain (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Using two or more languages in a singular context or conversation is similar to going with the flow these days, specifically on social sites. This is referred to as